Correction: Sequential inference as a mode of cognition and its correlates in fronto-parietal and hippocampal brain regions. - PLOS Computational Biology Staff (PLoS Computational Biology, 2017)
[This corrects the article DOI: 10.1371/journal.pcbi.1005418.].